2013
DOI: 10.3346/jkms.2013.28.8.1161
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model of the Cardiovascular System Coupling Heart Cellular Mechanics with Arterial Network Hemodynamics

Abstract: The current study proposes a model of the cardiovascular system that couples heart cell mechanics with arterial hemodynamics to examine the physiological role of arterial blood pressure (BP) in left ventricular hypertrophy (LVH). We developed a comprehensive multiphysics and multiscale cardiovascular model of the cardiovascular system that simulates physiological events, from membrane excitation and the contraction of a cardiac cell to heart mechanics and arterial blood hemodynamics. Using this model, we delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Adrenergic and muscarinic receptors mediate this process, and drugs can be antagonists at these receptors which may cause changes in indexes of contractility or other effects, such as beta‐blockers (beta1 adrenoreceptor antagonists), which are used in the treatment of hypertension. To further link AP with hemodynamics, models have been produced describing the electromechanics of the whole heart, and these have combined cell excitation/contraction (EC) coupled with heart mechanics, system circulation, and autonomic control . While great progress has been made defining multiscale systems approaches ( Figure ), these have not yet been fully utilized for linking drug exposure with cardiovascular changes for the assessment of safety or efficacy.…”
Section: Drug‐induced Changes On Hemodynamicsmentioning
confidence: 99%
“…Adrenergic and muscarinic receptors mediate this process, and drugs can be antagonists at these receptors which may cause changes in indexes of contractility or other effects, such as beta‐blockers (beta1 adrenoreceptor antagonists), which are used in the treatment of hypertension. To further link AP with hemodynamics, models have been produced describing the electromechanics of the whole heart, and these have combined cell excitation/contraction (EC) coupled with heart mechanics, system circulation, and autonomic control . While great progress has been made defining multiscale systems approaches ( Figure ), these have not yet been fully utilized for linking drug exposure with cardiovascular changes for the assessment of safety or efficacy.…”
Section: Drug‐induced Changes On Hemodynamicsmentioning
confidence: 99%
“…Safar et al [15] found that after adjustment for cofounders, only central pressure remained predictive in patients with renal failure. The Dicomano Study in Italy and a community based Taiwanese study also observed a stronger association between cardiovascular events and central, rather than brachial pressure [16,17] . Unfortunately with our study we did not have sufficient long term follow up to assess if elevated central blood pressure were indeed more predictive of adverse cardiovascular outcomes as compared to brachial blood pressure readings.…”
Section: Discussionmentioning
confidence: 89%
“…In view of the above and the information of Constanzo [1] and other literature review, Circulatory system can be represented as in figure 1. Similarly as per the information of Kim et al [21] and other literature review, Circulatory system can be represented as in figure 2. The symbols used are as follows: The resistance of a circuit consisting of series of resistances is the sum of individual resistances, whereas in case of parallel resistances; the inverse of system resistance is the sum of inverse of individual resistances.…”
Section: Physical Modelsmentioning
confidence: 99%
“…Resistances and Compliances of a few parts of the circulatory system are available in the paper published by Kim et al [21]. Volume of Blood stored in different parts of circulatory system and pressure at different points of circulatory systems are collected from Literature [1].…”
Section: Physical Modelsmentioning
confidence: 99%
See 1 more Smart Citation